Electronic Injection: Phase‐Controlled Synthesis of 1T‐MoSe2/NiSe Heterostructure Nanowire Arrays via Electronic Injection for Synergistically Enhanced Hydrogen Evolution (Small Methods 2/2019). Issue 2 (12th February 2019) - Zhang, Xing; Zhang, Yang‐Yang; Zhang, Yun; Jiang, Wen‐Jie; Zhang, Qing‐Hua; Yang, Yu‐Guo; Gu, Lin; Hu, Jin‐Song; Wan, Li‐Jun
Abstract : In article number1800317, Jin‐Song Hu and co‐workers report a phase‐controlled synthesis of 1T‐MoSe2 /NiSe heterostructure nanowire arrays. The conductive NiSe nanowire core can not only facilitate water dissociation and efficiently transport electrons, but also induce the formation of stable 1T‐phase MoSe2 nanosheet shell for enhanced hydrogen formation, synergistically boosting the overall alkaline hydrogen evolution.